Birds diversity at different elevation of mount Serapi (Kubah National Park), Sarawak - Nur Suhana, binti Razali. (Universiti Malaysia Sarawak (UNIMAS), 2007)
This study was carried out using mist-netting method to compare the diversity of birds at lower, middle and upper elevation and also to update the list of birds at Mount Serapi. From the total effort was with 5160 net hours, 355 individuals from 58 species were captured. The most dominant species at every elevation is Little Spiderhunter with total of 47 individuals. Species richness and Shannon Weiner diversity index were not significant different between elevations studied. However there were differences in species composition. For the checklist, this study has added another II species to Mount Serapi bird list. Eleven species are categorized as near-threatened and 4 species are endemic to Borneo.